A listening advantage for native speech is reflected by attention-related activity in auditory cortex [data] - Liang, Meng; Gerwien, Johannes; Gutschalk, Alexander (Universität, 2025)
The listening advantage for native speech is well known, but the neural basis of the effect remains unknown. We tested the hypothesis that attentional enhancement in auditory cortex is stronger for native speech using magnetoencephalography. Chinese and German speech stimuli were spoken by a bilingual speaker and combined into a two-stream, cocktail-party scene, with consistent and inconsistent language combinations. A group of native speakers of Chinese and a group of native speakers of German performed a detection task in the cued target stream. Results showed that attention enhanced negative-going activity in the temporal response function deconvoluted from the speech envelope. This activity was stronger when the target was in native compared to non-native language, and for inconsistent compared to consistent language stimuli. We discuss that the stronger activity for native speech could be related to better top-down prediction of the native speech stream.
Gefördert durch: Deutsche Forschungsgemeinschaft grant: DFG 593/5-1
Gesehen am 26.03.2025
Keywords: Forschungsdaten; Datenbank